Pengembangan Media Pembelajaran Bariumplants Pada Mata Pelajaran IPAS Kelas IV SDN Kamal 1 (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The purpose of this study was to develop bariumplants media that was valid, effective, and interesting for Class IV Science Science subjects at SDN Kamal 1. The subjects of this study were 3 grade IV students in small group trials, 24 students in field trials. The results showed that: 1) the average validity results from media expert validators, learning device design, learning materials were 87.6% with a very valid category. 2) the results of the effectiveness test were obtained through observing the teacher's activities, obtaining a percentage, namely 90% small group trials and 95% field trials. Observing student activities obtained percentages, namely 95% small group trials and 93.75% field trials. As well as student learning outcomes tests obtained by 24 students who were declared complete with scores above KKM 65 and classically student learning completeness obtained a percentage of 100% complete. 3) the results of the attractiveness test were obtained through a student response questionnaire in the small group test obtained 97.7% and the field test obtained 99.1% with a very interesting category. Based on the results of the research, the bariumplants media showed very valid, very effective, and very interesting criteria so that it could be used in science subjects Chapter 1 Plants are the Source of Life on Earth, Topic A Parts of Plant Body in class IV SDN Kamal 1.